Perception and impact of customized physical activity programs on objective physical activity parameters in prediabetes - Radhika Aditya Jadhav; G. Arun Maiya; Vidyut Rajhans; Shashikiran Umakanth; Shivashankara K N (Clinical Epidemiology and Global Health)
Background: Prediabetes is an established vital risk factor for Type 2 Diabetes Mellitus (T2DM), yet an under-recognized problem. The effectiveness of the Physical Activity Promotion Programme (PAPP) has rarely been studied extensively regarding objective Physical Activity (PA) assessment and subjective acceptance in prediabetes. The present mixed-method study evaluated the effect and perception of customized PAPP in prediabetes. Methods: The pre-post study included 54 prediabetes participants between 18 and 60 years of age who received the customized PAPP for 24 weeks. PA parameters were measured objectively using the tri-axial accelerometer Actigraph GT3X at baseline and the end of PAPP. Twelve participants were included in the qualitative study, and their perception of PAPP was explored using semi-structured telephonic interviews. Data analysis was done using a paired t-test and thematic analysis. Results: PA was significantly improved, which is evident in an increase in the average step count (MD = 1408), light activity duration (MD = 34.7 Min.), and moderate to vigorous PA duration (MD = 9.1 Min.). Average sedentary duration reduced significantly (MD = 32.46 Min.) (p < 0.05). Customized PAPP was happily accepted and continued by all the participants. Despite their challenging situations. Conclusion: Customized PAPP has yielded promising results, indicating its effectiveness in reducing sedentary duration and improving health parameters among prediabetic individuals. Customized physical activity interventions planned with due consideration of health parameters are crucial in enhancing health outcomes.